2013
DOI: 10.1158/2326-6066.cir-13-0035
|View full text |Cite
|
Sign up to set email alerts
|

Escalating Regulation of 5T4-Specific IFN-γ+ CD4+ T Cells Distinguishes Colorectal Cancer Patients from Healthy Controls and Provides a Target for In Vivo Therapy

Abstract: The relationship between the adaptive CD4 þ T-cell response and human cancer is unclear. The oncofetal antigen 5T4 is expressed in many human carcinomas, including colorectal cancer cells, but has limited expression on normal tissues. We previously identified anti-5T4 CD4 þ T cells in a proportion of patients with colorectal cancer, and we extended this study to examine whether the quality or quantity of the T-cell response reflects tumor stage. An overlapping peptide library spanning 5T4 was used as a target … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…Again, these results contrast with another study using 300 mg/m 2 CY in melanoma patients, which reported small, transient depletions of Treg cells . The differential effect could be due to the use of CY in patients with earlier stage cancers and hence lower tumour burdens; baseline frequencies of Treg cells in this patient group, although greater than healthy controls, was statistically lower than in patients with late‐stage melanoma, a finding also observed in colorectal cancer . A recent randomized controlled phase I/II study performed by our group administered low‐dose CY with or without a modified vaccinia Ankara‐based vaccine encoding the oncofetal antigen 5T4 (TroVax) to stage IV colorectal cancer patients, a notoriously poorly responsive tumour to immunotherapy .…”
Section: Cyclophosphamide For Cancer Immunotherapy – Clinical Studiescontrasting
confidence: 76%
See 3 more Smart Citations
“…Again, these results contrast with another study using 300 mg/m 2 CY in melanoma patients, which reported small, transient depletions of Treg cells . The differential effect could be due to the use of CY in patients with earlier stage cancers and hence lower tumour burdens; baseline frequencies of Treg cells in this patient group, although greater than healthy controls, was statistically lower than in patients with late‐stage melanoma, a finding also observed in colorectal cancer . A recent randomized controlled phase I/II study performed by our group administered low‐dose CY with or without a modified vaccinia Ankara‐based vaccine encoding the oncofetal antigen 5T4 (TroVax) to stage IV colorectal cancer patients, a notoriously poorly responsive tumour to immunotherapy .…”
Section: Cyclophosphamide For Cancer Immunotherapy – Clinical Studiescontrasting
confidence: 76%
“…determined that using CY in this manner actually augments anti‐tumour immunity in such patients through selective effects on CD4 + CD25 + Treg cells, allowing for greater tumour control . A number of studies have since used similar metronomic dosing regimens to limit Treg cell function to unmask tumour‐specific T‐cell responses . The dose of CY appears crucial to its immune‐potentiating effects as demonstrated in a clinical trial involving 28 patients with metastatic breast cancer: HER2‐specific antibody responses were enhanced following vaccination with a granulocyte–macrophage colony‐stimulating factor‐secreting breast tumour vaccine and CY administered at a dose < 200 mg/m 2 but higher dosages of CY suppressed these responses .…”
Section: Cyclophosphamide For Cancer Immunotherapy – Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphodepleting chemotherapy prior to immunotherapy reduces the number of circulating T regs , promotes successful engraftment of adoptively transferred T-cells, and improves the overall survival of melanoma patients [101]. Cyclophosphamide decreased peripheral FoxP3 + T regs in all six metastatic CRC patients and increased IFN-γ producing T-cells after 22 days [102]. Local ablation of immune cells using fludarabine, cyclophosphamide, and/or temozomide may dramatically increase the durability of ACT by reducing immunosuppressive pressures and widening a niche for tumor-specific T-cells.…”
Section: Directing the Immune System Against Metastatic Crcmentioning
confidence: 99%